2011
DOI: 10.1186/1477-3155-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Free Rhodium (II) citrate and rhodium (II) citrate magnetic carriers as potential strategies for breast cancer therapy

Abstract: BackgroundRhodium (II) citrate (Rh2(H2cit)4) has significant antitumor, cytotoxic, and cytostatic activity on Ehrlich ascite tumor. Although toxic to normal cells, its lower toxicity when compared to carboxylate analogues of rhodium (II) indicates Rh2(H2cit)4 as a promising agent for chemotherapy. Nevertheless, few studies have been performed to explore this potential. Superparamagnetic particles of iron oxide (SPIOs) represent an attractive platform as carriers in drug delivery systems (DDS) because they can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 40 publications
3
38
0
6
Order By: Relevance
“…Likewise, 10 to 100 nm are considered to be the ideal MNP diameters that avoid their recognition by the mononuclear phagocyte system, thus, allowing for a longer stay in the bloodstream, and promoting effective biodistribution. 3,29 In accordance with this desirable characteristic, maghemite nanoparticles used to prepare the magnetic nanocapsules evaluated in our study presented with a 10.0 nm (±2.5 nm) diameter, as observed by TEM micrograph. Further, the possibility of developing highly biocompatible polymericbased magnetic nanostructures using engineered maghemite nanoparticles 28 that are able to induce magnetohyperthermia was previously demonstrated.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Likewise, 10 to 100 nm are considered to be the ideal MNP diameters that avoid their recognition by the mononuclear phagocyte system, thus, allowing for a longer stay in the bloodstream, and promoting effective biodistribution. 3,29 In accordance with this desirable characteristic, maghemite nanoparticles used to prepare the magnetic nanocapsules evaluated in our study presented with a 10.0 nm (±2.5 nm) diameter, as observed by TEM micrograph. Further, the possibility of developing highly biocompatible polymericbased magnetic nanostructures using engineered maghemite nanoparticles 28 that are able to induce magnetohyperthermia was previously demonstrated.…”
Section: Discussionmentioning
confidence: 96%
“…23 The positive staining with annexin-V in cells is an indication of phosphatidylserine exposure in the plasma membrane, an event closely related to apoptosis. 3 A dose related increase was observed after 48 hours' treatment with MSE-NC (50 µg/mL of selol + 2.5 × 10 9 particles/mL (2X) and 200 µg/mL of selol + 1 × 10 10 particles/mL (8X)) while using breast cancer cells positively stained with annexin-V. Our findings are in very good agreement with the findings by Suchocki et al,20 which showed that the use of selol induced apoptosis in human leukemia cells. Apoptosis has been described as one of the more important mechanisms for the anticancer action of selenium-based compounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations